Managing New Industry Creation: Global Knowledge Formation and Entrepreneurship in High Technology - Levie, Reviewed by: Jonathan (Journal of International Business Studies, 2003)
Most scientific endeavour starts with puzzling empirical observations by scholars observing the world with open eyes and a critical mind. To investigate new phenomena, qualitative and longitudinal research is the first, often undervalued, stage of investigation. As international business scholars have come to prefer quantitative methods to qualitative methods, it is encouraging to find insightful qualitative work with the potential to stimulate the research in the field. The two books reviewed in this issue have this potential.